Formula delivery. - United States. Army. Signal Corps (photographer):::Creator::::::::::::; Flaherty, John Melvin (collector):::Contributor::::::::::::
Photograph shows a messenger delivering a bottle of baby formula to a mother at Fresno, California Assembly Center.